Marcas da exclusão e educação de jovens e adultos - Sa, Ingrid Rodrigues de (2021)
This research brings as a discourse to analyze the exclusion marks in the daily life of EJA students in the city of Santa Brígida - BA, it sought to analyze social, economic and cultural aspects that characterized the profile of students in the early years of elementary school in this modality. In this article, the main objective is to bring out, from the voices of students, feelings and self-perceptions that reveal exclusion marks, these marks being one of the most present characteristics in the profiles of these subjects. This is a case study carried out at Escola Simião Alves de Matos, in the urban area of the municipality of Santa Brígida-BA, involving students from 1st to 6th grade. The theoretical foundation of the research took as reference authors, such as Ponce (1998), Santos (2003), Capucho (2012), Arroyo (2017), Freire (2019) and Saviani (2019). This work will focus on aspects related to life trajectories, especially the educational and educational paths of EJA students, this work sought to contribute to discussions that consider times, spaces and contexts as triggers for learning and producers of student identity relations.